Directions for increasing the effectiveness of formation and development of socio-cultural potential in the system of economic growth of Ukraine (Economics and region, 2023)
The purpose of this article is to study the problems of the formation and development of socio-cultural potential in the system of economic growth of Ukraine and consider the directions of their solution. In the process of conducting scientific research, methods of analysis and synthesis, comparison and generalization were used. The purpose of this article is to study the problems of formation and development of socio-cultural potential. The work substantiates the statement that measures to increase the effectiveness of formation and development of socio-cultural potential must be considered in conjunction with measures for the growth of the economy of the country and its regions. It was noted that the formation and development of socio-cultural potential takes place under the influence of culture, national customs and traditions through the mediation of education, science, communications and other means of communication between people, the health care system, well-being, environment and other conditions have a significant impact on these processes for the work and living of the country's population. Emphasis is placed on the need in the post-war period to rapidly develop democracy, the legal system and civil society, education, science and culture, other areas of the spiritual life of society, to quickly solve problems that arise in the process of the interaction of the economic system with religious, moral, legal and other institutions. It is argued that in order to increase the efficiency of the formation of socio-cultural potential, it is necessary to introduce new methods, forms and models of the organization of education, to remove from educational programs, textbooks and manuals, other educational materials the entire Russian heritage, to study the true Ukrainian culture, the true and not distorted historical past, to overcome lagging education behind the faster development of science, departure from the Soviet principle regarding residual financing of education, science and culture, increase in salary and social status of teaching staff. The need for more active reform of the sphere of education, culture and the health care system, taking into account the needs of members of the united territorial communities and their characteristics, the introduction of the universal use of the Ukrainian language, the improvement of the ecological situation in the state, the reconstruction of the economy, educational and hospital institutions, and residential buildings was emphasized., elimination of all other consequences of this barbaric Russian-Ukrainian war. in the system of economic growth of Ukraine and consideration of directions for their solution. In the process of conducting scientific research, methods of analysis and synthesis, comparison and generalization were used.
Keywords: sociocultural potential; formation and development of sociocultural potential; management; economic growth; education; culture; health care